2020
DOI: 10.3390/pathogens9040281
|View full text |Cite
|
Sign up to set email alerts
|

A Global Analysis of Enzyme Compartmentalization to Glycosomes

Abstract: In kinetoplastids, the first seven steps of glycolysis are compartmentalized into a glycosome along with parts of other metabolic pathways. This organelle shares a common ancestor with the better-understood eukaryotic peroxisome. Much of our understanding of the emergence, evolution, and maintenance of glycosomes is limited to explorations of the dixenous parasites, including the enzymatic contents of the organelle. Our objective was to determine the extent that we could leverage existing studies in model kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Availability of much sequence data for diverse discoban protists allows us to add considerable depth to a timeline offered by Gualdrón-López et al (2012a) . Recently, Durrani et al (2020) reported a similar global bioinformatics approach. Caveats associated with estimating peroxisome localisation on a basis of detecting PTS motifs must be acknowledged: many peroxisomal and glycosomal proteins do not possess consensus PTS motifs; proteins with a PTS are often not detected in these organelles but elsewhere in a cell; and Güther et al (2014) , analysing the high-confidence proteome of epitope-tagged enriched glycosomes of PCF T. brucei , concluded use of PTS sequence searches in T. brucei has a sensitivity of <40% and a specificity of <50%.…”
Section: Discussion: Reconciling Bioinformatics Observations With a ‘...mentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of much sequence data for diverse discoban protists allows us to add considerable depth to a timeline offered by Gualdrón-López et al (2012a) . Recently, Durrani et al (2020) reported a similar global bioinformatics approach. Caveats associated with estimating peroxisome localisation on a basis of detecting PTS motifs must be acknowledged: many peroxisomal and glycosomal proteins do not possess consensus PTS motifs; proteins with a PTS are often not detected in these organelles but elsewhere in a cell; and Güther et al (2014) , analysing the high-confidence proteome of epitope-tagged enriched glycosomes of PCF T. brucei , concluded use of PTS sequence searches in T. brucei has a sensitivity of <40% and a specificity of <50%.…”
Section: Discussion: Reconciling Bioinformatics Observations With a ‘...mentioning
confidence: 99%
“…In searches, amino-acid sequences of known glycosomal proteins from different organisms provided queries to retrieve orthologues and paralogues from the following databases: TriTrypDB ( https://tritrypdb.org/tritrypdb/app ), AmoebaDB ( https://amoebadb.org/amoeba/app ), OrthoMCL DB ( https://orthomcl.org/orthomcl/app ), NCBI (National Center for Biotechnology Information, https://www.ncbi.nlm.nih.gov/ ) and DiscobaDB ( https://zenodo.org/record/5563074 ) ( Wheeler, 2021 ). Query sequences were adopted on a basis of glycosomal localisation from proteomic and genomic studies ( Colasante et al, 2006 , 2013 ; Güther et al, 2014 ; Morales et al, 2016 ; Acosta et al, 2019 ; Durrani et al, 2020 ; González-Robles et al, 2020 ; Quiñones et al, 2020 ; Jansen et al, 2021 ; Wheeler, 2021 ; Škodová-Sveráková et al, 2021 ) or the many biochemical and cell biological studies published previously. Sequence screening in DiscobaDB ( Wheeler, 2021 ) was done using Geneious Prime ® 2022.0.1 and BLASTp with default parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(Acosta et al, 2019; Colasante et al, 2006; Güther et al, 2014; Jardim et al, 2018; Vertommen et al, 2008). By bioinformatics analysis of genome sequence data, using potential peroxisome‐targeting signal (PTS) motifs as queries, the (partial) glycosomal localization of most of these metabolic processes has also been predicted for representatives of all other major kinetoplastid lineages (Butenko et al, 2020; Durrani et al, 2020). Remarkably, glycosomes of the TriTryps do not contain typical peroxisomal enzymes such as catalase, H 2 O 2 ‐producing D‐amino‐acid oxidase and α‐hydroxy‐acid oxidase, and glyoxylate cycle enzymes (Opperdoes, 1987).…”
Section: Figurementioning
confidence: 99%
“…Recently, we identified and characterized also the product of a gene, TcCLB.506945.20, that codes for a PAS–PGK in the T. cruzi strain CL-Brener Esmeraldo like. A PAS–PGK protein is also present in the genome of all other T. cruzi strains analysed (electronic supplementary material, table SI), and other kinetoplastids (table 3), except African trypanosomes [4,321]. The T. cruzi pas–pgk gene is on a different chromosome than the pgkA – pgkB/C gene array (figure 5).…”
Section: Diplonemid and Kinetoplastid Protistsmentioning
confidence: 99%
“…The absence of this PAS–PGK in African trypanosomes (such as T. brucei ), reported by us in previous studies [4], was also reported by Durrani et al . [321].…”
Section: Diplonemid and Kinetoplastid Protistsmentioning
confidence: 99%